Using molecular and culturing methods to study nitrifying microorganisms in peat - Daňková, Eliška (Jihočeská univerzita, 2023)
Soil samples from two peatland sites were analysed in order to determine the population of nitrifying microorganisms. Two DNA extraction methods were compared according to yield and an enrichment culture was used to attempt to isolate ammonia-oxidising organisms in a pure culture.
Using molecular and culturing methods to study nitrifying microorganisms in peat
Keywords: peatland soil; nitrification; bacteria; archaea; DNA extraction; 16S rRNA; culture; fen; spruce mire; peatland soil; nitrification; bacteria; archaea; DNA extraction; 16S rRNA; culture; fen; spruce mire